Knowledge and Attitude of Taif University Students on Stem Cell Banking - Alhomrani, Majid; Alamri, Abdulhakeem S.; Alsanie, Walaa F.; Alrobiey, Ashwag E.; Asiri, Raghad M.; Alaseri, Shahad M.; Alghamdi, Basmah K.; Almalki, Sara A.; Abdulaziz, Osama; Asdaq, Syed Mohammed Basheeruddin; Sreeharsha, Nagaraja (Indian Journal of Pharmaceutical Education and Research, 2022)
Background and Objectives: The awareness of university students is pivotal to the adaptation of new therapeutic technologies in combating illness and disorders. Stem cells are unique and effective in treating several pathological conditions. This study was an effort to determine the knowledge and attitude of Taif University students toward the banking of stem cells through the donation of umbilical cord blood (UCB). Materials and Methods: The study used a self-administered questionnaire that consisted of items on demographics, knowledge characteristics, and attitude towards banking of UCB as a source of stem cells for the purpose of achieving advanced therapeutic outcomes. The questionnaire was administered to only female students at Taif University during the academic year 2020-21. Both descriptive and inferential analysis were done using SPSSIBM 25 to analyze the data. Results: A total of 604 female students of Taif University responded to our questionnaire. Although most of the participants (70%) lacked sufficient knowledge (less than or equal to 2 out of 4), their attitudes were motivating, with more than 60% rated better than adequate (more than or equal to 3 out of 4). Many study participants have shown an interest in donating umbilical cord stem cells to treat other patients and for research purposes. Conclusion: Students with good knowledge of umbilical cord blood donation and those who are more educated showed a greater level of willingness to participate in banking and donation of stem cells. Therefore, raising awareness about stem cell banking and its importance among young undergraduates, especially female students, is imperative.
Keywords: Knowledge; Attitude; Taif University; Awareness campaigns; Umbilical Cord; blood